2008
DOI: 10.1108/09556220810850469
|View full text |Cite
|
Sign up to set email alerts
|

Optimized pattern grading

Abstract: Purpose -To evaluate current apparel industry Misses grading practices in providing good fit and propose grading practices to improve fit. Design/methodology/approach -Participants representing Misses sizes 6-20 based on ASTM D 5585 were selected. The fit of garments from traditionally graded patterns was assessed. Garments were fit-to-shape on participants. Traditionally graded patterns were compared to fit-to-shape patterns using quantitative and qualitative visual analysis. Findings -Current apparel industr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 7 publications
1
21
0
5
Order By: Relevance
“…Patterns that produce a well-fitting garment require attention to both body measurements and shapes (Hulme 1949, Ashdown et al 2003, Loker et al 2005, Bye et al 2008, Just-style.com 2010. Most patternmaking literature uses body measurements to specify pattern development for basic pant blocks and does not consider variations in specifications based on body shape.…”
Section: Relationship To Crotch Shape Categoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Patterns that produce a well-fitting garment require attention to both body measurements and shapes (Hulme 1949, Ashdown et al 2003, Loker et al 2005, Bye et al 2008, Just-style.com 2010. Most patternmaking literature uses body measurements to specify pattern development for basic pant blocks and does not consider variations in specifications based on body shape.…”
Section: Relationship To Crotch Shape Categoriesmentioning
confidence: 99%
“…Front darts ended at a range of points above and below the abdomen. Visual analysis (Bye et al 2008) of the layered crotch curves and patterns was completed to evaluate the relationship between body shape and dart length. Although some front darts ended below the abdomen landmark, they all ended before the body began to curve back inward under the abdomen.…”
Section: Dart Lengthmentioning
confidence: 99%
“…Studies carried out in UK [29] and Germany [6], show a 60% and 50% respectively of customers with difficulty to find proper clothes. In the same way, an anthropometric study performed in USA [9] to update the sizing ASTM standards also concluded that a 54% of the population was not satisfied with the fitting of the ready to wear (RTW) cloth [3]. Additionally, from the technological point of view, new 3D body scanning techniques constitute a step forward in the way of conducting and analyzing anthropometric data and contribute to promote new anthropometric surveys.…”
Section: Introductionmentioning
confidence: 99%
“…Apparel sizing using trimmed PAM and OWA operators M. V. Ibáñez (1) , G. Vinué (2) , S. Alemany (3) , A. Simó (1) , I. Epifanio (1) , J. Domingo (4) …”
mentioning
confidence: 99%
“…In the grading process, the ease allowance, shape, and body proportions are important factors that affect the garment silhouette and comfort. However, garment patterns are often graded using a planar pattern and it is thus difficult to make a garment while keeping the silhouette of the master pattern, especially in the case of a garment with a curved surface (Price and Zamkoff, 1996;Bye et al, 2008).…”
Section: Introductionmentioning
confidence: 99%